Adjunct Autophagy Suppression May Be a Promising Way to Eliminate the Resistance of Cancer Cells to Treatment: Autophagy saves the cancer cells - Mamizadeh, Zoleikha; Kalani, Mohamad Reza; Parsania, Masoud; Soltan Dallal, Mohammad Mehdi; Moradi, Abdolvahab (Archives of Medical Laboratory Sciences, 2021)
Background and Aim: Autophagy is a highly conserved mechanism in eukaryotic cells which removes the dysfunctional organelles from the cell. Autophagy has immense physiological and pathological roles in cells. There are a variety of reports showing the dual function of autophagy as a tumor suppression and promotion phenomenon. Therefore, targeted therapy approaches like virotherapy can be a promising cancer treatment. Vesicular stomatitis virus (VSV) is a well-known oncolytic virus which mutations in its matrix (M) protein including M51R, make it a better candidate for oncotargeting. Moreover, beclin-1 is one of the key regulators of autophagy and also apoptosis. Methods: In the present study, the level of autophagy markers such as beclin-1 and LC3 were investigated concerning the apoptosis process induction by VSV M-protein. Two colorectal cancer cell lines HCT116 and SW480 and one normal colon epithelial cell line (FHC) which expressing VSV M51R mutant M-protein were compared regarding autophagy versus apoptosis. All experiments were conducted at least in triplicate. Results: The results showed that the elevated level of caspase 3 and reduced amount of beclin-1 in transfected SW480 cells may be an acceptable description for apoptosis. Conclusion: In HCT116 cells domination of autophagy, plays a supportive mechanism for the cells to survive in response to M51R M-protein stress. Suppression of autophagy as an adjunct can be a promising way to eliminate resistance to cancer treatment. We have quantitively evaluated the Beclin-1 and LC3-II as autophagy markers, Future evaluation of these two along with other markers like P62 will reduce the limitations of this study. *Corresponding Authors: Dr. Mohamad Reza Kalani; Email: kalani@goums.ac.ir; ORCID: https://orcid.org/0000-0002-8756-1200 Dr. Abdolvahab Moradi; Email: dr.moradi@goums.ac.ir; ORCID: https://orcid.org/0000-0003-2877-4190 Please cite this article as: Mamizadeh Z, Kalani MR, Parsania M, Soltan Dallal MM, Moradi A. Adjunct Autophagy Suppression May Be a Promising Way to Eliminate the Resistance of Cancer Cells to Treatment. Arch Med Lab Sci. 2021;7:1-11 (e24). https://doi.org/10.22037/amls.v7.35678